Vitrifikasi Blastosis Mencit dengan Metode Kriolupv ?O - Batan, I Wayan; Suatha, I Ketut; Esti PrasetyoningtyaserB, Wahono; Handayani, Nining; Djuwita, Ita; Boediono, Arief (Jurnal Veteriner; Vol 10 No 4 (2009))
Cryopreservation is an ultra rapid freezing process to preserve tissue or organ. The study was conducted to identify the effectiveness of cryoloop vitrification method and the viability of embryos following vitrification. Embryos at blastocyst stage were vitrified by placing them in equilibration medium containing 10% ethylene glycol (EG) and phosphate buffer saline (PBS) wich supplemented with 20% new born calf serum for 8-10 minutes. The blastocysts were then removed and put in vitrification medium (15% dimethyl sulfoxide, 15% EG, and 0.5M sucrose), and the process in the vitrifivcation medium not longer than 25-30 seconds. The blastocysts were immediately transferred to the vitrification medium film in the cryoloop and plunged into 100 ml liquid nitrogen. The warming process was done by immersing the cryoloop which carried the vitrified blastocsts into PBS supplemented with 20% serum and 0.5M sucrose for 1 minute, and then removed to same solution supplemented with 0.25M sucrose and 0.1M sucrose for 2 minutes respectively. The blastocysts were washed 4 times in kalium simplex optimized medium (KSOM) and cultured in drops of KSOM in 5% CO2 incubator at 370C. The observations were done every 6 hours for 48 hours using inverted microscope ( Olympus IX70 Japan). The viability of embryos was assessed on the basis of the intact morphology, reexpansion of the blastosul, and the development of embryos into advance stage. The results showed that 85.71% of vitrified embryos, developed into advance stages and 19% of them hatched. In conclusion the cryoloop can be used to vitrify the embryos.
Keywords: vitrification, blastocyst, cryoloop